NERACA KARBON PADA SISTEM PERTANIAN BERBASIS PENGGUNAAN ABU SISA DARI BAKARAN DI LAHAN GAMBUT PEDALAMAN (Studi kasus pada Budidaya Tanaman Jagung (Zea mays L. Saccharata) di Kalampangan) (Carbon Balance in Farming systems Based the Use of Ash of Burnt on Inland Peat : The Case Study on Cultivation of Corn (Zea mays L. Saccharata) in Kalampangan) - P.,, Surawijaya,; vita, Yo (AGRIPEAT, 2017)
ABSTRACTThis study aims to: (1) analyzing the balance of carbon in the combustion materials to produceash burnt on the cultivation of corn plants (2) analyze the effect of the ash of burn on thephysical and chemical properties of peat ombrogen. The results showed that the net balanceobtained from this study is negative, this is because the value of the carbon is lost during anemissions in the combustion process wood / roots, weeds urchins and groundcover plants priorto obtaining the ashes of burnt of litter is 0.607 t of carbon/ha is larger than the value of thecarbon that is successfully moored by weeds urchins 0.057 t of carbon/ha and litter previouscrop (great chili plant litter) is 0.11 t of carbon/ ha, only 21,41% carbon successfully tethered.Keywords: Balance of carbon, peat ombrogen, ash ameliorant and sweet corn crops.